Analisis Perbedaan Tingkat Konservatisme Akuntansi Sebelum dan Sesudah Konvergensi IFRS (Studi Empiris pada Perusahaan Manufaktur yang terdaftar di BEI Tahun 2008-2009 dan 2012-2013) - Lidia Marselina; Nurzi Sebrina (Wahana Riset Akuntansi, 2016)
This study aimed to analyze the differences of accounting conservatism before and after the convergence of IFRS. This research was a comparative research that aims to compare the presence of one or more variables at two or more different samples or more than one. This study used secondary data obtained from the site www.idx.co.id. The population in this research manufacturing companies listed on the Indonesian Stock Exchange (IDX) during the years 2008-2009 and 2012-2013 as many as 174 companies. This study used purposive sampling technique and obtain 59 manufacturing companies. The data in this study were tested using the Kolmogorov Smirnov normality and hypothesis testing using the Wilcoxon Signed Rank Test. This study used two methods of measurement that the accrual and changes in operating income. The results of the two methods showed that there is no difference of accounting conservatism before and after the convergence of IFRS. Keywords:accountingconservatism,IFRS convergence